DEVELOPMENT OF KEY COMPETENCE OF FUTURE TEACHERS OF PEDAGOGICAL DISCIPLINES - Shapran, O. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. The necessity of the formation of competence of teachers in the process of training at higher education institutions. Purpose is to identify ways of developing key competences of future teachers in the process of teaching disciplines. Results. The essence and main features of key competences personality are determined. We considered the variety of key competencies in current European programs: DeSeCo, TUNING. «Key competences for lifelong learning.European information system». We analyzed the classification of key competencies of famous scientists (I. Zymnia, H. Selevko, A. Khutorskii). The conclusion about the absence of a single coherent classification of key competencies is made. Importance of social and personal competencies of experts as a kind of key is proved. Originality. The possibilities of development of key competence in the process of teaching their subjects through interdisciplinary integration are considered. The necessity to identify common educational courses of the leading ideas that provide the opportunity to develop professional skills, abilities, experience is proved. We proposed the complex of problematic tasks that actualize students’ knowledge of the history of pedagogy and general pedagogy. We discovered new possibilities of interdisciplinary integration of in a magistracy, which summarizes students’ knowledge obtained during the study of various subjects in previous courses, establish different causal educational ties. We proposed the using of the problematic tasks of integrated nature in the process of studying the course «Pedagogy of high school». Conclusion. There have been proved the necessity of stimulating of cognitive activity of students in the process of training through the use of various interactive gaming technologies. We defined the developing the potential of role playing games, where students act starring "scholars", "critical", "artist", "experts", "coordinators" and so on. We proposed the business simulation games in teaching of pedagogical disciplines, for the enforcement of actions of students and teachers, parents and class teacher, the director and his deputies and others. It was determined that the integration of educational disciplines and application of innovative learning technologies contribute to forming a system of knowledge of students a high level of generality, effectiveness and practicality of their key competencies.